A child with a severe headache: Answers - Telhan, Leyla; Beğenik, Murat; Yaman, Yöntem; Yavaşcan, Önder (Springer Science and Business Media Deutschland GmbH, 2021)
1) What is your suspected diagnosis of acute severe headache in this patient? We report here an adolescent girl who presented with severe headache while receiving acute sinusitis treatment and was found to have bilateral papilledema, anemia, hepatosplenomegaly, and hypertension. In addition, our patient also manifested the symptoms and signs suggesting increased intracranial pressure as intractable headache, nausea, vomiting, and bilateral papilledema.
Keywords: Child; Headache; Intracranial Hypertension; Pseudotumor Cerebri; Systemic Lupus Erythematosus